Movements and diving behavior of Risso’s dolphins in the Southern California Bight - Rone, Brenda K.; Sweeney, David A.; Falcone, Erin A.; Watwood, Stephanie L.; Schorr, Gregory S. (Frontiers in Marine Science, 2022)
Risso’s dolphins (Grampus griseus), uncommon prior to the 1970’s, are now regularly observed within the Southern California Bight. During long-term cetacean monitoring programs on United States Navy range areas in the Southern California Bight from 2009–2019, we deployed 16 Argos-linked satellite tags on Risso’s to acquire objective, detailed depictions of their movements and behaviors. Individuals were tracked for a median of 10.7 days (range = 0.8 – 19.7). Kernel density estimation suggested individuals utilized the entire Southern California Bight with the 50% core use area centered around San Clemente and Santa Catalina Islands where most of the tag deployments occurred. Grand median dive depth was 101 m (max = 528) and dive duration was 5.6 min (max = 11.1). We used generalized mixed models to assess seasonal and environmental effects on distribution and diving behavior including month, distance to shore, time of day, lunar phase, sea surface temperature, and chlorophyll-a residuals. Animals were further from shore (including islands) during a full versus new moon and from the mainland during the last versus first quarter moon. Animals also tended to be closer to land in the fall and early winter months. Dives were deeper yet shorter during the night, during a full moon, and when animals were further offshore. Animals conducted nearly twice as many dives at night compared to day, though deep dives (> 500 m) occurred at all times of day. This study provides insights into Risso’s distribution and behavioral trends while identifying priorities for future research.